O desempenho ocupacional e as relações com o lazer na vida da pessoa com deficiência física - Loren Salles Souza Pereira (2016)
Considering the latest data from the Brazilian Institute of Geography and Statistics (IBGE) for the census of the 2010 year, more than 45.6 million of Brazilians reported having some type of disability. The number represents 23.9% of the total population. In the state of Minas Gerais the figure is about 22.6% and in Belo Horizonte, they account for 23.2% of the population. People with disabilities, by law, have the same rights as people without disabilities, however, they cannot always guarantee their rights under the same conditions as people without disabilities, due to the disadvantages imposed by the restriction features and the society which imposes them to physical, legal and attitudinal barriers. These barriers are responsible for the gap in the implementation of the rights of people with and without disabilities. This situation allows us reflect on the unequal participation conditions in which people with and disabilities live. Reflecting on leisure in the conditions that most of the people with disabilities live means to reflect on their fundamental right as a citizen. To substantiate actions and public policies that meet the needs and rights of people with disabilities it is necessary to know these people and understand the environmental and contextual factors that influence the participation of this population in leisure activities. This research aimed to verify the facilitators and restrictive aspects of the participation of 10 people, with acquired disabilities, wheelchair users, in leisure activities in Belo Horizonte. Thus, it was applied the Canadian Occupational Performance Measure (COPM) that evaluates the self-perception of people with disabilities about their occupational performance and a socioeconomic questionnaire. Disabilities are understood as a condition that is part of human diversity. Therefore, the research focused on studying the personal and environmental factors that influence the restriction or participation on social life, specifically at leisure. The study identified some factors that influence participation in recreation activities that are: architectural barriers, socioeconomic barriers and attitudinal barriers.